2016
DOI: 10.1016/j.jasc.2016.07.129
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Neoplasms to the Pancreas Diagnosed by Fine Needle Aspiration/Biopsy Cytology: A 15-Year Retrospective Analysis

Abstract: Background Metastatic tumors to the pancreas are rarely encountered and diagnostically challenging. We aspired to determine the incidence and origin of all metastases to the pancreas at our institution, and to examine their clinicopathologic and cytomorphologic features. We also sought to ascertain the effect of endoscopic ultrasound (EUS) guidance implementation. Methods A search of our database was undertaken to review all pancreatic FNA and/or CNB examined from January 2000 through December 2014. Results Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Out of 4955 adult autopsy cases in the same study, there were 190 cases of pancreatic tumors, none with MCC. Raymond et al 16 reported a single case of MCC among 221 patients who were diagnosed with a pancreatic malignancy via FNA/core needle biopsy. Primary pancreatic neoplasm is an important differential for MCC metastatic to pancreas, especially with isolated pancreatic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 4955 adult autopsy cases in the same study, there were 190 cases of pancreatic tumors, none with MCC. Raymond et al 16 reported a single case of MCC among 221 patients who were diagnosed with a pancreatic malignancy via FNA/core needle biopsy. Primary pancreatic neoplasm is an important differential for MCC metastatic to pancreas, especially with isolated pancreatic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to laboratory finding, various imaging tools including CT, MRI, positron emission tomography (PET), and EUS are very sensitive and useful diagnostic methods. On CT/MRI, primary pancreatic cancer is incline to have dilated pancreatic duct and pancreatic atrophy, while metastatic pancreatic cancer tends to have pancreatic head involvement, well-demarcated margins, tumor necrosis, central attenuation, and peripheral enhancement, 7 which are often mimicking a pancreatic neuroendocrine tumor. PET scan has an advantage in identifying occult metastatic lesions which cannot be detected by conventional CT or MRI imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmatory immunochemical staining including S-100, Sox-10, HMB-45, Melan-A, and MITF can be employed to aid the diagnosis. 7 Most patients with metastatic pancreatic cancers have very poor prognosis due to widespread disease. Less than 5% of patients with metastatic pancreatic cancers have localized pancreatic metastatic lesions, and they may have improved outcomes from surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…4 Pancreatic metastases account for 0.7%-11.1% of all FNAs, and 1.8%-10.8% of all pancreatic malignancies. 5 Most patients with secondary tumors of the pancreas often have metastases to other organs and are considered challenging cases for the surgical treatment option. The rate of metastatic tumors confined to the pancreas is very low and surgical treatment can be considered an option in cases with isolated pancreatic metastases.…”
Section: Introductionmentioning
confidence: 99%
“…It is very useful for the detection of metastatic primary origin with a history of the extrapancreatic tumor 4 . Pancreatic metastases account for 0.7%–11.1% of all FNAs, and 1.8%–10.8% of all pancreatic malignancies 5 . Most patients with secondary tumors of the pancreas often have metastases to other organs and are considered challenging cases for the surgical treatment option.…”
Section: Introductionmentioning
confidence: 99%